A Philosophical Stimulation in Early Professionalization of Medicine in Buenos Aires, 1820-1842 - Di Pasquale, Mariano (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
This article examines the texts produced by the so-called “ideologues” from Rio de la Plata according to identify emerging connections between them and the European intellectual currents, in particular, those notions derived from Destutt de Tracy and Pierre Jean Georges Cabanis. It seeks to demonstrate that the dissemination of this knowledge through the classrooms of the University of Buenos Aires will have a crucial importance in the incipient formation of Buenos Aires medical science in the first half of the 19th century. This knowledge is articulated with the need to renew the medical knowledge in the framework of the Republican political system of Government. In the field of scientific and academic, medicine should also be one-piece modified and adapted to the guidelines of the new political order, which provoked an incipient process of professionalization of the activity and the need to put the medicine within the parameters of modern science.